MEMUTUS LOGIKA KARITATIF DALAM PRAKTIK PARIWISATA DI UBUD, BALI - I Made Kusuma Negara; I Made Adikampana; Saptono Nugroho (Jurnal Kawistara, 2017)
Many villas in Ubud is located around agricultural land owned by farmers who are members of Subak. There is a deal that the villas are required to provide material contributions to local institutions, including Subak. Such contributions produce caritative framework which not in line towards the sustainability of tourism development. This paper addresses to offer the guidelines of sustainable tourism practice in Ubud, Bali. To fulfill this purpose, data has been collected from observations and interviews with selected informants and then analyzed descriptively. The analysis indicated that there is dualism perspective against agriculture, which has implications towards exclusivity in-group, especially farmers and villas. Each group attempts to maintain the dualism perspective by applying various tactics, which can lead to disharmonies relations between groups. It requires social guidance in order to reduce caritative framework by creating common tourism sphere through agrotourism.